MORTALITY AND SALE PATTERN OF SONADI SHEEP IN ITS NATIVE TRACTS (Indian Journal of Animal Production and Management, 2016)
The present study was conducted in four districts i.e. Udaipur, Chittorgarh, Rajsamand and Bhilwara from  breeding tract of Sonadi sheep. The data on flock statistics of 6979 registered Sonadi sheep maintained  by 147 shepherds of eight tehsils from four districts of Sonadi breeding tract were recorded. The overall  mortality according to different seasons and age groups of Sonadi sheep was highest during summer  (57.0%) as compared to winter (15.7%) and rainy (27.3%) seasons. Sonadi sheep belonging to age group  of 1-3 month, 3-6month and adult, the frequency of mortality was highest during summer, while in case of  sheep belonging to age group of above 6 months mortality was in rainy season. The maximum proportion  sheep’s were sold in the month of July in Udaipur and in the month of May in Chittorgarh districts. Higher  proportion of sheep were sold during summer as compared to winter and rainy seasons, while the sheep’s  belonging to age group of 1-3 months, 3-6 months and adult were sold during summer season. The overall  literacy rate had significant effect on all the parameters of land holding as well as buffalo, goat, total sheep,  large ruminant, small ruminant and total livestock holding. The positive and significant association was  observed between age of family head and total cattle, total other than Sonadi sheep and large ruminant  population. The correlation of literacy rate with buffalo, goat, large ruminant and total livestock was found  to be positive and significant.
Keywords: Mortality; Native tract; Sale; Sheep